FACTORS OF PALM OIL HARVESTERS PRODUCTIVITY - Ahmad Zuhryansyah; Muhammad Nurali; Delyana Rahmawany Pulungan; Antonio Mario Sipayung; Purjianto (RADJA PUBLIKA, 2022)
Work productivity is a way to measure how well the workforce performs and the production power used to obtain the work results that the individual or company wants to achieve. The aim of this research is to determine the level of harvester productivity at PT. Gunung Mas Raya and Knowing the factors that influence harvester productivity at PT. Mount Mas Raya. The research method used is quantitative descriptive analysis method. The sample determination method was carried out using simple random sampling, the division sample determination was carried out randomly. The data collection techniques used were interviews, documentation and questionnaires using the Guttman scale based on indicators (age, work experience, number of dependents, highest level of education, premium). Data analysis techniques use validity tests, reliability tests, Multiple Linear Regression tests, t tests, f tests and coefficient of determination. Data processing in this research used SPSS software (version 25). Based on the research results, it shows that work experience and number of dependents influence productivity, while age, highest level of education and premiums do not influence productivity at PT. Mount Mas Raya.